Seasonal differences in food and nutrient intakes among young children and their mothers in rural Burkina Faso - Arsenault, Joanne E.; Nikiema, Laetitia; Allemand, Pauline; Ayassou, Kossiwavi A.; Lanou, Hermann; Moursi, Mourad; De Moura, Fabiana F.; Martin-Prével, Yves (Cambridge University Press, 2014)
It is important to understand and account for seasonal variation in food and nutrient intakes when planning interventions to combat micronutrient deficiencies in resource-poor settings. The objective of the present study was to quantify food and nutrient intakes and assess the adequacy of micronutrient intakes among young children and their mothers during the lean and post-harvest (PH) seasons in rural Burkina Faso. We quantified food intakes by 24-h recall in a representative sample of 480 children aged 36–59 months and their mothers in two provinces in Western Burkina Faso. We calculated the probability of adequacy (PA) of usual intakes of ten micronutrients and an overall mean PA (MPA). Seasonal changes in nutrient intakes and PA were assessed by mixed linear regression and non-parametric tests, respectively. Energy intakes did not differ significantly between seasons for women or children, although the women's intakes were slightly higher in the PH season. Most of the micronutrient intakes were significantly higher in the PH season, with the exception of vitamin A which was lower and vitamin B12 and Zn which were similar across seasons. MPA increased significantly across seasons, from 0·26 to 0·37 for women and from 0·43 to 0·52 for children. PA of Ca, vitamin C, folate and vitamin B12 were very low. Staple grains and vegetables were major sources of micronutrients but intakes were not sufficient to meet nutrient needs for the majority of the subjects. Food-based strategies are needed to increase micronutrient intakes of women and children in Burkina Faso.